Establishment of trauma registry at Queen Elizabeth Central Hospital (QECH), Blantyre, Malawi and mapping of high risk geographic areas for trauma - Chokotho, L; Mulwafu, W; Nyirenda, M; Mbomuwa, F; Pandit, H; Le, G; Lavy, C (Zhejiang University, 2018)
Background: Less attention is directed toward gaining a better understanding of the burden and prevention of injuries, in low and middle income countries (LMICs). We report the establishment of a trauma registry at the Adult Emergency and Trauma Centre (AETC) at Queen Elizabeth Central Hospital (QECH) in Blantyre, Malawi and identify high risk geographic areas. Methods: We devised a paper based two-page trauma registry form. Ten data clerks and all AETC clinicians were trained to complete demographic and clinical details respectively. Descriptive data, regression and hotspot analyses were done using STATA 15 statistical package and ArcGIS (16) software respectively. Results: There were 3,747 patients from May 2013 to May 2015. The most common mechanisms of injury were assault (38.2%), and road traffic injuries (31.6%). The majority had soft tissue injury (53.1%), while 23.8% had no diagnosis indicated. Fractures (OR 19.94 [15.34–25.93]), head injury and internal organ injury (OR 29.5 [16.29–53.4]), and use of ambulance (OR 1.57 [1.06– 2.33]) were found to be predictive of increased odds of being admitted to hospital while assault (OR 0.69 [0.52–0.91]) was found to be associated with less odds of being admitted to hospital. Hot spot analysis showed that at 99% confidence interval, Ndirande, Mbayani and Limbe were the top hot spots for injury occurrence. Conclusion: We have described the process of establishing an integrated and potentially sustainable trauma registry. Significant data were captured to provide details on the epidemiology of trauma and insight on how care could be improved at AETC and surrounding health facilities. This approach may be relevant in similar poor resource settings.